الدور المستقبلي للقاضي الإداري في ظل تحولات القانون الإداري - بن عبد الله, عادل (University of Eloued جامعة الوادي, 2018)
The article of the study presents the future role of the administrative judge in light of the changes of administrative law. So that the relations between the administration and the society have undergone significant shifts, imposing reconsideration and arranging the institutions of administrative law, and seeking in the role of the administrative judge. Today’s talks has no longer about an administrative law as a body of roles that are fundamentally different from the private law, which finds its mains source in jurisprudence. so that the abundance of legal texts and the impact of constitutional law led on one hand to the decline of the creative role of the administrative judge in posing the rules and the restriction of the scope of the administrative judiciary by devolution of many management disputes for normal justice. All this raises a fundamental question on which role left to the administrative judge in making the administrative law.
الملتقى الدولي الثامن: التوجيهات الحديثة للقضاء الإداري ودوره في إرساء دولة القانون 06-07 مارس 2018 جامعة الوادي
Keywords: الإجتهاد القضائي، القضاء الإداري، القانون الإداري